Presuppositions in the Podcast Titled "Kalau Dinar Candy... Apanya Mau Dibungkam Coba, Dah Kacau Dr Sana Nya…” on Deddy Corbuzier’s YouTube Channel - Salma, Adhe’qu Mia Nabila; Anggraini, Dewi Esa; Muniroh, Ihdatul; Rumilah, Siti; Fidiyanti, Murni; Fi’aunillah, Tristy Kartika (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study analyzes presuppositions in interactions on a YouTube channel, using a case study of a podcast video featuring Deddy Corbuzier and Dinar Candy. The research employs a pragmatic approach based on Yule’s theory. The aim is to identify the types of presuppositions and their impact on communication dynamics. A qualitative descriptive method is used to analyze the utterances in the video. The expected outcome is to broaden the understanding of various types of presuppositions and their influence in digital interactions, particularly on YouTube channels. The findings of this study are expected to contribute to linguistic studies, especially in the field of Pragmatics, by exploring presuppositions in digital (social media) interactions.